O discurso de mulheres educadoras na imprensa paraibana: tessituras do processo histórico de escolarização na Paraíba (1930 - 1939) - Silva, Shirley Targino (2017)
This dissertation is inserted in the molds of the reflexive process on women’s history in Brazil, more specifically in Paraíba from 1930 to 1939, and make possible to articulate, in a dimensional fashion, the women’s history to the educational phenomenon called schooling. The objective is to analyze the enrollment of the educators Analice Caldas de Barros, Albertina Correia de Lima and Alice de Azevedo Monteiro in the historical schooling process of Paraíba, by means of their writings in the “Boletins de Educação” and “Revista do Ensino” periodic publications. The research builds upon the concept of schooling as established by Luciano Mendes Faria Filho, which converges to the concept of cultural education as defined by Antônio Carlos Ferreira Pinheiro. There for, schooling is conceived as an organized education, tied to a systemized network, as well as the expectations we hold in relationship to the world and the people; expressed in our beliefs; developed in the various situations lived by each individual; in the displays of (in)civility of the human being and in the capacity for socialization, defining itself as a continued process. The schooling process is not reduced to the school institution, other perspectives also define it, the interchange of popular knowledge and sociocultural practices, such as: reading and writing of pedagogic press. The dialogue among the New Cultural History, women’s history, and the winding of the tactics by Michel de Certeau and Pierre Mayol as to the arts of making, living and cooking, was the basis for the theoretical methodological contribution. In the search to prestige women’s history, it is highlighted the contribution of the educators, searched in this dissertation, to Paraiba’s educational scenery, as they founded an association for feminine progress, lectured in various stages of the scholar teaching, fought for the emancipation and for the feminine suffrage, wrote in the press, publicizing their ideas and ideals, permeated spaces that were masculine before, among other actions. Facing what was exposed, it is possible to affirm that the aforementioned educators contributed as much for the schooling process as for the process of sociocultural change and in the debate for gender equality in Paraíba going against relations of power.